Eco on networks: the reverberation of misogynistic practices that occurred on the Discord platform (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Permeating the daily life of part of the population, social networks endorse an unprecedented advance. However, hyperconnected and free in cyberspace, some users find an environment for unethical actions. In this way, the present work, through a bibliographic review, seeks to understand the digital environments as facilitators for misogynistic practices, bringing from the perspective of content analysis a clipping of the Fantástico report on the crimes that occurred on Discord. Finally, instructions and effects related to hyperconnectivity and freedom on networks are discussed, understanding that malicious information goes beyond the virtual, causing reverberations in the private life of victims.
Keywords: social networks; Information Science; misogyny; Discord